TOTALLY CHLORINE-FREE BLEACHING OF SODA RAPESEED PULP - Potůček, František; Říhová, Martina (Technická univerzita vo Zvolene, 2018)
Soda pulp cooked from rapeseed straw was subjected to the totally chlorine-free bleaching using hydrogen peroxide and peractic acid as bleaching agents. The five-stage bleaching sequence, Q1Q2EPPaaP, containing two chelation stages, as well as four-stage sequence, AEPPaaP, with an acidic stage were applied to investigate the properties of bleached soda pulp, namely its brightness and tensile strength. For comparison, once-dried kraft softwood pulp, as well as never-dried oxygen-predelignified kraft softwood pulp and sulphite spruce pulp were bleached under the same process conditions. The results obtained showed that totally chlorine-free bleaching did not bring the sufficient bleaching effect for soda rapeseed pulp. The brightness of 54 % ISO achieved for the AEPPaaP bleaching sequence was lower comparing to that for kraft and sulphite pulps.
Bezchlorové bělení natronové řepkové buničiny
Keywords: soda rapeseed pulp; TCF bleaching; brightness; breaking length; natronová řepková buničina; TCF bělení; bělost; tržná délka